Realisasi Banten Saiban Di Desa Adat Tanjung Benoa Badung (Perspektif Pendidikan Agama Hindu) - I Made Agus Sukara (Cetta: Jurnal Ilmu Pendidikan, 2019)
Every religion in the world has various religious ceremonies to offer to God, as well as Hinduism which cannot be separated from religious ceremonies to connect themselves to Ida Sang Hyang Widhi Wasa and all His manifestations. The existence of religious ceremonies in Bali has so many unique uniqueness, one of which is Banten Saiban located in Tanjung Benoa Traditional Village, South Kuta District, Badung Regency. The uniqueness of Banten Saiban in Tanjung Benoa Indigenous Village is Banten Saiban which only numbered six pieces with various contents in it and used bokoran for its place. The results showed that the realization of the Saiban Banten in Tanjung Benoa Indigenous Village was that people made six sacrifices of pelinggih, pelangkiran bale, natar rumah, song-sombah, more houses and stoves. The ingredients used in making sacrifice saiban have symbols namely bokoran, leaves or apron, rice, side dishes, salt, vegetables, snacks or snacks, water and coffee. The uniqueness of this saiban is found in the manufacturing process as the ingredients are placed in a separate place even though they are still in one bokoran and use rice that is clad in advance. Banten Saiban is delivered every day after cooking in the morning. The value of education contained in Mebanten Saibanya is the value of Tattwa education, the value of moral education or ethics, the value of social education.